PCB mounted sensor with high sensitivity SWNT-Based devices for gas sensing applications. (May 2021) - Kumar, Narendra; Navani, Naveen Kumar; Manhas, Sanjeev Kumar
Abstract: In this paper, the fabrication of aligned semiconducting single-walled carbon nanotube (SWNT) devices on a thermally grown silicon dioxide (SiO2 ) over silicon (Si) substrate is presented. The SWNTs are aligned between the nickel fingers that are patterned on the substrate. Subsequently, the fabricated devices are bonded onto a low-cost printed circuit board (PCB) with wire bonder. The mounted sensors have been tested for carbon dioxide (CO2 ) gas, acetone, and isopropyl alcohol (IPA) vapor sensing at room temperature. The sensitivity values of 27% for the concentration of 15000 ​ppm of CO2, 52% for the concentration of 7000 ​ppm of acetone, and 67% for the concentration of 900 ​ppm of IPA have been observed with good response and recovery times. The fabricated sensors show better performance than the already reported sensors. Graphical abstract: Image 1